Criminal moves modes of mobility in crime fiction - Gulddal, Jesper ca. 20./21. Jh (Liverpool University Press, 2020)
Criminal Moves is a ground-breaking collection of essays that challenges the distinction between literary and popular fiction and proposes that crime fiction is a genre that constantly violates its own boundaries. Reorienting crime fiction studies towards the mobility of the genre, it has profound ramifications for how we read individual crime stories
Description based on publisher supplied metadata and other sources
Keywords: Kriminalroman; Electronic books; Aufsatzsammlung